Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5005/jp-journals-10024-1024
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Variations of Maxillary Molars Palatal Root and the Importance of Its Knowledge for Endodontic Practice: A Case Series

Abstract: Aim: The present report describes and discusses root canal variations in the internal morphology of maxillary molars.Background: Dental internal anatomy is directly related to all the technical stages of the endodontic treatment. Even though, in some situations a typical anatomical characteristics can be faced, and the professional should be able to identify them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…In a case series in which five teeth, maxillary first and second molars, with bifurcated palatal canals were identified, the authors highlighted that the assumption of a single canal in all palatal roots of maxillary molars needs to be changed [ 32 ]. Within this context, a study [ 33 ] identified five cases of second molars with two or three canals in the palatal root. The findings of the present study corroborate the results of these authors since variations were observed in the morphology of the palatal canal, especially when the classification proposed by Vertucci [ 15 ] was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case series in which five teeth, maxillary first and second molars, with bifurcated palatal canals were identified, the authors highlighted that the assumption of a single canal in all palatal roots of maxillary molars needs to be changed [ 32 ]. Within this context, a study [ 33 ] identified five cases of second molars with two or three canals in the palatal root. The findings of the present study corroborate the results of these authors since variations were observed in the morphology of the palatal canal, especially when the classification proposed by Vertucci [ 15 ] was used.…”
Section: Resultsmentioning
confidence: 99%
“…In a case series in which five teeth, maxillary first and second molars, with bifurcated palatal canals were identified, the authors highlighted that the assumption of a single canal in all palatal roots of maxillary molars needs to be changed [32]. Within this context, a study [33] identified five cases of second molars with two or three canals in the palatal root.…”
Section: E Scientific World Journalmentioning
confidence: 99%
“…22 This tool can be especially useful when it is possible to identify independent entrances for each canal. 23 Buhrley et al 24 concluded that when the maxillary first molars were considered separately, the frequency of MB2 canal detection for the microscope, dental loupes, and no magnification groups were 71.1%, 62.5%, and 17.2%, respectively. Baldssari-Cruz et al 25 evaluated 39 maxillary molars in vitro and concluded that the surgical operating microscope did aid in the identification of mesiolingual canal orifices.…”
Section: Case Reportmentioning
confidence: 99%
“…Ozcan, Aktan e Ari (2009) descreveram a incomum anatomia de um segundo molar superior com três canais mésiovestibulares. Em outro estudo, Scarparo et al (2011) identificaram cinco casos de segundos molares com dois ou três canais na raiz palatina, além de duas raízes palatinas distintas. Zhao et al (2011) apresentou um caso de um segundo molar com três raízes mésiovestibulares e outro de um terceiro molar com quarto raízes independentes.…”
Section: Revisão Da Literatura E Discussãounclassified